Error field measurement, correction and heat flux balancing on Wendelstein 7-XaNotice: This manuscript has been authored by Princeton University under Contract Number DE-AC02-09CH11466 with the U.S. Department of Energy. The publisher, by accepting the article for publication acknowledges, that the United States Government retains a non-exclusive, paid-up, irrevocable, world-wide license to publish or reproduce the published form of this manuscript, or allow others to do so, for United States Government purposes. (10th March 2017) - Lazerson, Samuel A.; Otte, Matthias; Jakubowski, Marcin; Israeli, Ben; Wurden, Glen A.; Wenzel, Uwe; Andreeva, Tamara; Bozhenkov, Sergey; Biedermann, Christoph; Kocsis, Gábor; Szepesi, Tamás; Geiger, Joachim; et al.
Abstract: The measurement and correction of error fields in Wendelstein 7-X (W7-X) is critical to long pulse high beta operation, as small error fields may cause overloading of divertor plates in some configurations. Accordingly, as part of a broad collaborative effort, the detection and correction of error fields on the W7-X experiment has been performed using the trim coil system in conjunction with the flux surface mapping diagnostic and high resolution infrared camera. In the early commissioning phase of the experiment, the trim coils were used to open an n / m   =  1/2 island chain in a specially designed magnetic configuration. The flux surfacing mapping diagnostic was then able to directly image the magnetic topology of the experiment, allowing the inference of a small  ̃4 cm intrinsic island chain. The suspected main sources of the error field, slight misalignment and deformations of the superconducting coils, are then confirmed through experimental modeling using the detailed measurements of the coil positions. Observations of the limiters temperatures in module 5 shows a clear dependence of the limiter heat flux pattern as the perturbing fields are rotated. Plasma experiments without applied correcting fields show a significant asymmetry in neutral pressure (centered in module 4) and light emission (visible, H-alpha, CII, and CIII). Such pressure asymmetry is associated with plasma-wall (limiter) interaction asymmetries between the modules. Application of trim coil fields with n   =  1 waveform correct the imbalance. Confirmation of the error fields allows the assessment of magnetic fields which resonate with the n / m   =  5/5 island chain.